PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN SENI MUSIK DI SMP NEGERI 1 SUNGAYANG KAB. TANAH DATAR - Fauziah Rahman; Ardipal Ardipal; Yensharti Yensharti (FBS Universitas Negeri Padang, 2018)
Abstract This study aimed to determine whether there were differences in student learning outcomes both using audio visual media and without using audio visual media in music art learning in SMP Negeri 1 Sungayang. The type of this research was quantitative research with experiment method. The design in this study was Pretest - Posttest Control Group Design. The population in this study were all students of class VIII, amounting to 108 students. The sample in this research was determined by random sampling technique and obtained class VIII.5 as experiment class and class VIII.1 as control class. Moreover, independent variables were the use of audio visual media and the use of conventional media, while the dependent variable was the result of student learning in the subject of art and culture, especially art of music. The research data was obtained from multiple choice test of ensemble music material on pretest and posttest. Validity test and reliability test used Kuder Richardson (KR 20). In this research, t-test was used as technique of data analysis. Data obtained from the results of pretest and posttest then processed using Microsoft Excel 2010 program. The results showed that the results of experimental classroom learning by using audio visual media was better than classroom control classroom learning results using conventional media. There was a significant difference between learning outcomes taught by using audio visual media with learning outcomes using conventional media in art learning. This was evidenced from the calculation of t-test obtained tcount 3.2932> ttable 2.0195. The application of audio-visual media in the learning of music art can improve students’ learning outcomes for the better, this was evidenced from the average increase in experimental class learning outcome was 87.73 and the average control class was 82.86. Thus, it was obtained the difference in the average of experimental class and control class of 4.87. Keywords: Aplication, Audio Visual Media, Music Art Learning